The relationship between organizational culture and total quality management in SMEs - Hernandez Chavez, Gerardo; Jaramillo Villanueva, José Luis; Hernández Chávez, Yazmín (Estudios de Administración, 2022)
Organizational Culture is widely recognized as one of the fundamental elements for the successful implementation of Total Quality Management, which is not always easy to harmonize. Therefore, it is necessary to promote the development and commitment of workers towards quality and productivity. The purpose of this work is to analyze the correlation between Organizational Culture and the implementation of Total Quality Management practices through an empirical study in small and medium-sized companies in the clothing industry in the state of Tlaxcala, Mexico. The study is quantitative and cross-sectional through the application of the Competence Values Framework to assess Organizational Culture and the model of the European Foundation for Quality Management to examine Total Quality Management. The information was obtained through a survey addressed to executives of the participating companies, and the data analyzed through descriptive statistics, Pearson’s correlation, and simple regression analysis. The findings support a positive correlation between Organizational Culture and the implementation of Total Quality Management practices. The limitations of this study are its sectoral nature and the fact that it is restricted to a specific territory.